2021
DOI: 10.1111/ene.14940
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multimorbidity and its impact on survival in people with motor neuron disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Only one case-control study 28 31 With exceptionally high rates of case ascertainment (>95%) and extensive clinical phenotyping, the register has enabled researchers to investigate several important questions about MND. 32 Of particular note, Leighton et al 30 reported analysis from the Scottish National MND register, finding that the standardised incidence in Scotland was 67% higher even than the Northern European estimates in 2015-2016. 30 MND specialist nurses are ideally placed working in localised areas.…”
Section: Introductionmentioning
confidence: 99%
“…Only one case-control study 28 31 With exceptionally high rates of case ascertainment (>95%) and extensive clinical phenotyping, the register has enabled researchers to investigate several important questions about MND. 32 Of particular note, Leighton et al 30 reported analysis from the Scottish National MND register, finding that the standardised incidence in Scotland was 67% higher even than the Northern European estimates in 2015-2016. 30 MND specialist nurses are ideally placed working in localised areas.…”
Section: Introductionmentioning
confidence: 99%